THE EFFECT OF QUERCETIN AND GALANGIN ON GLUTATHIONE REDUCTASE - Paulikova, Helena; Berczeliova, Elena (Biomedical papers, 2005)
Quercetin and galangin can change the activity of glutathione reductase. Quercetin (a catechol structure in the B-ring) and galangin (any hydroxyl group in the B-ring) have different biological activities but, both possess high antioxidant abilities. Quercetin during the antioxidative action, is converted into an oxidized products (o-semiquinone and o-quinone), and subsequently glutathionyl adducts may be formed or SH-enzyme can be inhibited. We have tried to see whether inhibition of glutathione reductase (GR) can be influenced by preincubation of enzyme with NADPH (a creation of reduced form of enzyme, GRH2) and whether diaphorase activity of the enzyme is decreased by these flavonoids. The results confirmed that quercetin inhibits GRH2 and inhibition is reduced by addition of EDTA or N-acetylcysteine. Both of flavonoids have no effect on diaphorase activity of glutathione reductase and this enzyme could increase the production of free radicals by catalysis of reduction of o-quinone during action of quercetin in vivo.
Keywords: Flavonoids/ Glutathione reductase/ Diaphorase activity.